PENGARUH INSENTIF DAN PENERAPAN ABSENSI FINGER PRINT TERHADAP KINERJA KARYAWAN PT. JAYA MASAWAN PUTERA SEJAHTERA PADA STORE PASARAYA BANDUNG - Yasmina Martini; Ulil Amri (JURNAL KOMPETITIF, 2021)
This study examines the performance of employees of PT. Jaya Masawan Putra Sejahtera Pasaraya Bandung Palembang. The purpose of this study was to determine and prove whether the provision of incentives and fingerprint attendance had an effect either simultaneously or partially on employee performance. The population in this study were 169 employees and the sampling technique used by the Slovin formula was 119 employees. The technique of collecting data is through the distribution of closed questionnaires. The research instrument data were tested for validity and reliability. The analysis technique uses inferential statistics with multiple linear regression equations, then the regression coefficient, correlation coefficient and determination coefficient are carried out. Hypothesis testing through F-test and t-test both to see the effect simultaneously or partially. The significance level is 5%, the data processing media is through the SPSS version 20 program.The results of data analysis obtained a correlation (r) between incentives and fingerprint attendance with employee performance of 0.993 or 99.30% which means that the relationship between incentives and fingerprint attendance with employee performance has a strong and significant relationship, and R2 is 0.985 or 98 ,50% means that the variation in employee performance is explained by the provision of incentives and the remaining fingerprint attendance (100% - 98.50% = 1.50%) is explained by other factors such as motivation, work discipline, work performance and work climate . Multiple linear regression equation : = 0.273 + 0.493 X1 + 0.581 X2 + e. F-Test results obtained Fhit value of 38.329 with the level of Sig. 0.000, because the value of Sig,F <0.05, it proves that presenting incentives and fingerprint attendance has an effect on employee performance. The results of the t-test obtained thit value 9,460 with Sig.0,000 <0.05 for presenting incentives, thit value 13,087 with Sig.0,000<0.05 for fingerprint attendance partially affects employee performance.